Fast Parameter Identification of the Fractional-Order Creep Model - Shabnam Tashakori; Andres San-Millan; Vahid Vaziri; Sumeet S. Aphale (Actuators)
In this study, a parameter identification approach for the fractional-order piezoelectric creep model is proposed. Indeed, creep is a wide-impacting phenomenon leading to time-dependent deformation in spite of constant persistent input. The creep behavior results in performance debasement, especially in applications with low-frequency responses. Fractional-Order (FO) modeling for creep dynamics has been proposed in recent years, which has demonstrated improved modeling precision compared to integer-order models. Still, parameter uncertainty in creep models is a challenge for real-time control. Aiming at a faster identification process, the proposed approach in this paper identifies the model parameters in two layers, i.e., one layer for the fractional-order exponent, corresponding to creep, and the other for the integer-order polynomial coefficients, corresponding to mechanical resonance. The proposed identification strategy is validated by utilizing experimental data from a piezoelectric actuator used in a nanopositioner and a piezoelectric sensor.